Use of Collagen and Fibroblasts in Modern Medicine (Review of Literature) (Eurasian Research Bulletin, 2023)
The work is devoted to a review of the options for the use of collagen and materials based on collagen in medicine and the pharmaceutical industry. The problem of effective impact on the local manifestation of the wound process and at the present stage of development of medicine remains unresolved, despite the emergence of various drugs and techniques. Among the many types of cells that can have a clinical effect, of particular interest are dermal fibroblasts, which are a heterogeneous population of mesenchymal cells and play a key role in the regulation of cell interactions and maintaining skin homeostasis. Currently, there are more than 60 modern cellular or tissue drugs for the treatment of wounds, which makes it difficult to choose an appropriate, safe and effective adjuvant therapy. A review of the world literature on the role of collagen in the wound healing process is presented. The problems of the epidemiology of chronic wounds and ulcers of various origins, the physiology and pathophysiology of the phases of wound healing are considered. The pathogenetic role of different types of collagens, as well as the mechanisms of functioning of collagen, macrophages, fibroblasts, matrix metalloproteinases, and other cytokines during ulcer healing, are discussed